2020
DOI: 10.1111/ctr.13887
|View full text |Cite
|
Sign up to set email alerts
|

Donor thyroid hormone therapy is associated with an increased risk of graft dysfunction after heart transplantation

Abstract: ObjectiveHeart transplantation (HT) is uniquely associated with the potential impact of thyroid hormone therapy at three intersecting levels—donor, operation, and recipient. We aimed to study the effect of thyroid hormone therapy of the donor on primary graft dysfunction (PGD).MethodsA retrospective cohort study was conducted on 209 HT recipients assessed from 1997 to 2018; for 33 of the recipients, the donors had received T4 (DT4 group), and for 176, the donors had not (NoDT4 group). The primary endpoint was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Thyroxine replacement was associated with early graft loss and 30-day mortality by analyzing data from 23,000 HTX recipients [ 30 ]. The withdrawal phenomenon has been hypothesized in this process as after implantation the heart will be placed in a relative thyroid hormone deficiency of the recipient caused by sick euthyroid syndrome, amiodarone treatment and glucocorticoid treatment [ 31 ]. Reliable data from prospective studies are still missing regarding the benefit of thyroid hormone replacement.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroxine replacement was associated with early graft loss and 30-day mortality by analyzing data from 23,000 HTX recipients [ 30 ]. The withdrawal phenomenon has been hypothesized in this process as after implantation the heart will be placed in a relative thyroid hormone deficiency of the recipient caused by sick euthyroid syndrome, amiodarone treatment and glucocorticoid treatment [ 31 ]. Reliable data from prospective studies are still missing regarding the benefit of thyroid hormone replacement.…”
Section: Discussionmentioning
confidence: 99%
“…38 Nonetheless, concerns have been raised regarding an early withdrawal effect that is associated with a higher risk of PGD in heart transplant recipients whose donors had received TH therapy. 16 Similarly, there are studies suggesting that donor T4 administration is detrimental to liver transplant recipients, for whom higher peaks of transaminases, higher rates of graft dysfunction and failure, and a greater need for post-operative plasmapheresis have been reported. 17,18 The conclusions of these studies have found support in recent studies in mice showing that both steroids and thyroxine have detrimental effects on the reperfused steatotic liver, with thyroid supplementation being associated with increased rates of hepatic necrosis.…”
Section: Donor Th Protocols and Formulationmentioning
confidence: 99%
“…Recently, it has been hypothesized that an early withdrawal effect in HTx recipients whose donors had received TH therapy could be associated with primary graft dysfunction (PGD). 16 Higher peak transaminases and higher rates of graft dysfunction and failure have also been reported in liver transplant recipients of livers procured from donors receiving hormonal therapy. 17,18 The primary aim of this study was to test the hypothesis that donor TH therapy is independently associated with early graft loss (EGL) in a large contemporary cohort of HTx recipients, a finding that would support the TH withdrawal effect hypothesis.…”
mentioning
confidence: 97%
“…Thyroid hormones affect cardiac electrophysiology, contractility, and vasculature. SH is associated with an increased risk of coronary heart disease (CHD), especially in subjects under 65 (5)(6)(7)). An independent association was found between fT4 and adverse outcomes after HTx, and perioperative low fT4 levels could be a prognostic marker of adverse outcomes in HTx (8).…”
Section: Introductionmentioning
confidence: 99%